A mathematical modeling of free wave motions in the Sea of Azov - Shul’ga, T.Ya. (Reports of the National Academy of Sciences of Ukraine, 2014)
With the use of a three-dimensional nonlinear hydrodynamic model, which describes the turbulent motion a viscous liquid, the physical regularities of free vibrations is given in the aquatorium of the Sea of Azov. Changes of the amplitudes of fluctuations of the level are studied, and their comparison for off-shore districts and the central area is executed. The type of nodal lines and their transformation in time are researched. The speeds of arising flows at various depths are determined.